2014
DOI: 10.1111/ppl.12300
|View full text |Cite
|
Sign up to set email alerts
|

Spectral effects of LEDs on chlorophyll fluorescence and pigmentation in Phalaenopsis ‘Vivien’ and ‘Purple Star’

Abstract: We examined the effect of light emitting diode (LED) lighting in greenhouse facilities on growth, chlorophyll fluorescence and pigmentation in Phalaenopsis 'Vivien' and 'Purple Star' under purpose-built LED arrays yielding c. 200 µmol m(-2)  s(-1) at plant height for 14 h per day and 24/18°C day/night temperature, respectively, from January to April 2013. The light treatments were (1) 40% blue in 60% red (40% B/R), (2) 0% blue in 100% red (0% B/R) and (3) white LEDs with 32% blue in white (32% B/W, control), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
33
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 50 publications
7
33
0
5
Order By: Relevance
“…Light is an important factor for the production of pigments and exposure to different light qualities triggers different physiological responses (Ouzounis et al, 2015). In this study, we found that light quality affected the chlorophyll a/b ratio and carbohydrate content ( Table 2).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Light is an important factor for the production of pigments and exposure to different light qualities triggers different physiological responses (Ouzounis et al, 2015). In this study, we found that light quality affected the chlorophyll a/b ratio and carbohydrate content ( Table 2).…”
Section: Discussionmentioning
confidence: 56%
“…Hogewoning et al (2010b) found that Fv/Fm and ΦPSII of plants grown under blue light and combinations of red and blue light were significantly higher than those grown under red light, yet Fv/Fm and ΦPSII of plants had no significant difference between blue light and combinations of red and blue light, and in addition, monochromatic red light resulted in dysfunctional photosynthetic machinery. Ouzounis et al (2015) also reported that the Fv/Fm of phalaenopsis sp. grown under red light alone was significantly lower than the Fv/Fm of plants grown under a mixture of red and blue light.…”
Section: Discussionmentioning
confidence: 99%
“…In Phalaenopsis, it has been reported that reddish leaves formed under increasing B light (Ouzounis et al, 2014). Leaf coloration is affected by many factors with varying effects (Sims and Gamon, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of LEDs on a great deal of horticultural [lettuce (Shen et al, 2014), cucumber (Hernández and Kubota, 2016), basil (Bantis et al, 2016)] and ornamental [Phalaenopsis (Ouzounis et al, 2014)] plants has already been studied. However, only a few studies have been conducted using forest tree species as test material (Astolfi et al, 2012;Riikonen, 2016;Smirnakou et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the fact that red lighting has been proved to influence the photosynthetic ability, plant biomass, and plant growth (Kim et al, 2004), it was not applied together with blue lighting. The whole premise behind using pure blue LED light in combination with natural or supplemental light is based on our previous studies (Ouzounis et al, 2014a,b), which have shown that additional blue light increases the amount of SMs; however, those studies were performed almost solely with LEDs as supplemental light.…”
Section: Introductionmentioning
confidence: 99%